If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -3n = 9n + 2 Reorder the terms: 11 + -3n = 2 + 9n Solving 11 + -3n = 2 + 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. 11 + -3n + -9n = 2 + 9n + -9n Combine like terms: -3n + -9n = -12n 11 + -12n = 2 + 9n + -9n Combine like terms: 9n + -9n = 0 11 + -12n = 2 + 0 11 + -12n = 2 Add '-11' to each side of the equation. 11 + -11 + -12n = 2 + -11 Combine like terms: 11 + -11 = 0 0 + -12n = 2 + -11 -12n = 2 + -11 Combine like terms: 2 + -11 = -9 -12n = -9 Divide each side by '-12'. n = 0.75 Simplifying n = 0.75
| 157=113-u | | 2(x+19)=x+29 | | 4+4x=x | | -9t+-7(-6+-10)= | | 2(x+9)=x+29 | | y-47=-41 | | x-40=30 | | 22=9n-(-4) | | 6(n-4)=-54 | | 4(m-2)=1 | | 13=6+6 | | log[5]3+log[5]t+log[5](t+4)=log[5]63 | | -2(10x-1)=-48-10x | | 2(x+2)=3x-8 | | 16-7x=-61 | | 10m+9n+4m= | | -4+6(-6+10h)-4h= | | 1.8d+3=2(.9d-1.5) | | A(x)=2x+8x+14 | | 3m+7=7m+6 | | -12+5k=15-45 | | (9x-6)+(3x+8)= | | 7(2+9g)= | | 7.50x+4.75x=891.25 | | 6(3+5y)+(y-8)=13 | | f(x)=-5x+5 | | -10(-2s+1)+6= | | -3x-10=-9x-2 | | log[b](y-3)-log[b](y-4)=log[b](y+3)-log[b]y | | -8a+7(1+5a)=-17+3a | | -5+20x+5x+10=180 | | 5y-1=2y |